2015
DOI: 10.19030/jabr.v31i4.9295
|View full text |Cite
|
Sign up to set email alerts
|

Interlinkage Between Real Exchange Rate And Current Account Behaviors: Evidence From India

Abstract: The study analyzes the dynamic interlinkage between India's real effective exchange rate and real current account deficit using standard VAR and structural VAR (SVAR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Therefore, when the exchange rate depreciates, the price of imported goods becomes relatively more expensive, resulting in a current account deficit. These results support [25], [29], [32], [33], which stated that the currency rate significantly and negatively affects the CA balance. However, this finding contrasts with the works of [17], [34], [35] who find a positive impact of currency rate on current account balance.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, when the exchange rate depreciates, the price of imported goods becomes relatively more expensive, resulting in a current account deficit. These results support [25], [29], [32], [33], which stated that the currency rate significantly and negatively affects the CA balance. However, this finding contrasts with the works of [17], [34], [35] who find a positive impact of currency rate on current account balance.…”
Section: Resultssupporting
confidence: 82%
“…The findings showed that the currency rate had a significant and negative effect on the CA. Similarly, [32] examined the effect of the exchange rate on the current account in India between 1975 and 2011 using VAR analysis. Their results showed that the currency rate appreciation causes a decrease in the CA balance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, empirical studies such as Arouri et al (2014) and Lee and Chinn (2006) revealed a negative relationship between currency devaluation and the current account balance. Arouri et al (2014) examined the dynamic interaction between real effective exchange rate and real current account deficit in India using VAR and impulse response, and suggested that real currency depreciation worsens the current account balance. In contrary to the conventional wisdom, a positive shock to the real exchange rate, i.e.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…This eventually brings us to the conclusion that these nations' current account deficit was unmaintainable and failed to move towards external-account equilibrium. Arouri et al (2015) focussed on analysing the sensitivities of current account deficit in response to real exchange rate based on annual data series throughout 1975 to 2011. The study revealed that a rise in rupee exchange rate lowers current account imbalance and it further emphasised the disturbances in the form of productivity shocks, technological advancements and changes in consumer behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%